Isolasi dan Identifikasi Bakteri Asam dari Rebung Fermentasi Tradisional dari Desa Panti - Nyimas Fatiyah Aini; Ardi Mustakim (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
Traditional bamboo shoot fermentation is a hereditary practice still preserved by the people of Panti Village, Pasaman Regency. This process not only serves as a natural preservation method but also makes an important contribution to the formation of distinctive flavors and increases the nutritional value of bamboo shoots. One key aspect of this fermentation process is the activity of microorganisms, particularly lactic acid bacteria, which play a role in the production of metabolites such as lactic acid, which functions as a natural preservative, inhibits the growth of pathogenic microbes, and contributes to the distinctive flavor and aroma of fermentation. The main objective of this study was to isolate and identify the types of lactic acid bacteria found in traditionally fermented bamboo shoots. Fermented bamboo shoot samples were taken from several local production houses in Panti Village. The microbial isolation process was carried out using selective media MRS (de Man, Rogosa, and Sharpe) agar, which is commonly used for the growth of lactic acid bacteria. The obtained isolates were then analyzed through colony morphology observation, Gram staining, and microscopic tests to determine initial characteristics. Further identification was carried out through a series of biochemical tests to determine the genus and species of the bacteria. The results of the study showed the presence of several Gram-positive, rod-shaped bacterial isolates that are strongly suspected to belong to the lactic acid bacteria group, such as Lactobacillus plantarum. This bacterium is known to have probiotic potential and functional benefits in fermented food products. These findings indicate that traditional fermented bamboo shoots can be a potential source of functional bacterial isolates that are beneficial for the food industry, particularly in the development of probiotic products, natural preservatives, and food additives based on local fermentation. This study emphasizes the importance of preserving local wisdom in food fermentation practices as a foundation for sustainable, culturally aware food technology innovation and supporting food security based on local resources.